Climate Change Impact on Water Availability and Water Balance on Sampit Sub-Cachtment, Central Kalimantan - Sulistyani, Kiki Frida; Irianto, Danang Bimo (Universitas Tribhuwana Tunggadewi Malang, 2024)
Sampit River is part of the Mentaya catchment area, located in the East Kotawaringin Regency, Central Kalimantan, Indonesia. Sampit River is generally used as a water supply for domestic, industrial, and livestock needs. The Mentaya River water balance shows that for the year 2030 projection, the Sampit River is expected to experience a deficit, specifically during the first period of the month of October. This research was conducted using the SSP 1 2.6 climate change scenario. In this scenario, it is estimated that rainfall will change from +2.282 to +1.020% and increase in temperature ranging from 0.441-0.793 oC within the period 2021-2030 to 2041-2050. The calculation of 90% dependable flow shows climate change impacts the period of the year 2030 to 2050 when compared to the existing dependable flow. Likewise, the 95% dependable flow for river maintenance, also increases. The research concludes that the water balance endures climate change impact and the calculated deficit remains the same for the first period of the month of October. The results of the water balance show that until 2050 climate change had not impeded negative effects but cautionary efforts must be taken as there an increasing deficits for the years 2040 and 2050. Â